2017
DOI: 10.1111/poms.12686
|View full text |Cite
|
Sign up to set email alerts
|

Improving Profits by Bundling Vertically Differentiated Products

Abstract: We consider a firm managing a category of vertically differentiated goods, that is, products which differ with respect to an attribute for which all consumers prefer more to less. The goods can be sold individually, in which case they are referred to as components, or in bundles. The firm chooses the assortment of components and bundles and their selling prices to maximize profit. We show that each bundling strategy (pure components, pure bundling or mixed bundling) can be optimal and obtain closed‐form expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…To understand which is more valuable by consumers, bundles or individual products is the first subject under research. This understanding is relevant, as several authors advocate distinct scenarios: bundling is widely implemented for information goods and online services because it can increase profit for companies (Ye et al 2017); bundling is an effective strategy for companies to increase revenues (Honhon and Pan 2017); bundles generally are not preferred over separate products (Knutsson 2011).…”
Section: Individual Products or Bundlesmentioning
confidence: 99%
“…To understand which is more valuable by consumers, bundles or individual products is the first subject under research. This understanding is relevant, as several authors advocate distinct scenarios: bundling is widely implemented for information goods and online services because it can increase profit for companies (Ye et al 2017); bundling is an effective strategy for companies to increase revenues (Honhon and Pan 2017); bundles generally are not preferred over separate products (Knutsson 2011).…”
Section: Individual Products or Bundlesmentioning
confidence: 99%
“…Prior studies have found that PB could be more profitable (compared to MB) because of network externality (Prasad et al , 2010), limited supply of a product (Cao et al , 2015), bundling vertically differentiated products (Honhon and Pan, 2017), or negatively correlated reservation prices and high starting inventory levels (Bulut et al , 2009). This work has produced the following important and interesting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in an e-retailer-dominated Stackelberg market, according to (18) and (19), the supply chain's optimal profit, denoted by π(p r 12 , w r 12 ), is:…”
Section: E-retailer-dominated Stackelberg Modelmentioning
confidence: 99%
“…In particular, they determine wholesale prices and optimal offline/online prices. Honhon et al [19] consider vertically differentiated goods that can be sold individually or in bundles and described optimal bundling strategies. Sarkar et al [33] apply the Stackelberg game policy to determine sales strategies for two products.…”
mentioning
confidence: 99%